Migrace za životním stylem surfaře v marocké vesnici Taghazout a změny, které způsobuje v místním prostředí - Remešová, Lucie (Lidé města, 2023)
In this article, I describe my research in the Moroccan village of Taghazout, where I traced the causes and consequences of significant changes stemming from tourism and lifestyle migration over a period of more than a decade. Originally a fishing village with almost no tourism, it became a sought-after center for surfers from all over the world and a location for foreign investors, which completely changed the character of the site. A large number of these surfers are so-called lifestyle migrants who have permanently settled in Taghazout and formed an international community here – they are mainly British, Dutch, German, French, and Spanish. First, I reflect on my own multi-layered position in the field, and then I focus on surfing as the cause of these changes and the main motive of lifestyle migration. I describe it in terms of the subculture and a lifestyle sport. After that, I focus on lifestyle migration and sports tourism, which are very closely related topics. In the actual analysis of data from the field, I deal with the development of Taghazout itself, and I deal with the types of lifestyle migrants settled in the village, who are most often surfers. I focus more closely on their psychology, motivations, and the types of surfers in the context of the surfing mentality. Finally, I describe the very effects of tourism and migration on the local environment, which include the influx of alcohol and drugs into the village, the effect on bodily exposure, and caring for the environment.